CONTINUOUS TRAINING OF MAKING AUTOMATIC SEMI PUMP EQUIPMENT OF HORTICULTURE PLANTS FOR INCREASING PRODUCTIVITY OF FARMERS IN KOTA GAJAH DISTRICT, CENTRAL LAMPUNG - Telaumbanua, Mareli; Lanya, Budianto; Haryanto, Agus; Suharyatun, Siti; Rahmawati, Winda (Batoboh, 2019)
Insect pests generally attack horticultural plants and carry viruses that are harmful to plants. For this reason, a tough and precise control system is needed to be able to control insect pests. Researchers from the University of Lampung have designed a semi-automatic insect pest trapping device utilizing solar energy that can control the development of pest insects in horticultural crops. Technology that is transformed to the public has affordable assembly costs with great benefits to reduce the effects of crop failure from insect pests. The aim of this service is technological transformation through continuous socialization, training, manufacturing, and maintenance of semi-automatic pest traps from the University of Lampung. This service is carried out for horticultural producers in the Maju farmer group, Kota Gajah Subdistrict, Central Lampung. The working system of this tool At night, ultraviolet lamps and TL lights installed are able to attract insect pests to come around the lights and fall into the trap. Whereas during the day, the scent of attractant and fermomon is able to attract insect pests to be ensnared. The technology used has been integrated with electricity sources from renewable energy, namely solar cells.